Analysis of The Non-Compatibility of Geomorphological Conditions Towards Flash Flood VulnerabilityiIn Anai Valley - Lidia Mewilda; Ratna Wilis; Ajidirman; Rosdianto; Nana Sutrisna (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
Flash floods are a hydrometeorological disaster that frequently occurs in mountainous watersheds, particularly in areas with land use that is not in accordance with its natural geomorphological conditions. This study aims to analyze the geomorphological characteristics of the Anai Valley, determine the level of flash flood vulnerability based on the integration of biophysical parameters, and assess the contribution of geomorphological mismatches to increasing flash flood vulnerability. This study uses a Geographic Information System (GIS) approach with a weighted overlay method through the integration of slope gradient, soil type, land use, river buffer, and rainfall parameters. The results show that the Anai Valley area is dominated by steep to very steep slopes, volcanic and alluvial soil types, and land use activities that develop along the Batang Anai River. High to very high flash flood vulnerability zones are concentrated in the valley plains and river corridors. Land use mismatches on steep slopes and river boundaries contribute significantly to increased surface runoff and environmental degradation.